Global impact of Occupational Noise-Induced Hearing Loss (ONIHL): trends, gender disparities, and future projections: 1990–2036 - Dandan Liu; Huixia Ji; Ye Chen; Wenying Li (Frontiers in Global Women's Health)
BackgroundThe burden of Occupational Noise-Induced Hearing Loss (ONIHL) is escalating globally, presenting significant challenges to society and healthcare systems. This study aims to provide a comprehensive assessment of the global burden of ONIHL from 1990 to 2021, analyze these impacts by gender, and project the future burden of ONIHL over the next fifteen years.MethodsThe data were sourced from the Global Burden of Disease (GBD) study conducted in 2021. A Joinpoint regression model was employed to calculate the annual percentage change (APC) in ONIHL Years Lived with Disability (YLDs) rate, and a decomposition analysis was utilized to quantify the influences of age structure, population growth, and epidemiological changes on the global burden of ONIHL. Additionally, predictions of future YLDs rate trends were made using Bayesian Age-Period-Cohort (BAPC) and Autoregressive Integrated Moving Average (ARIMA) models.ResultsThe global rate of ONIHL YLDs escalated from 3,838,055 person-years in 1990 to 7,847,445 person-years in 2021, with an age-standardized YLDs rate experiencing a 23% increase. Males exhibited a higher number and rate of YLDs than females, however, the growth rate for females was greater, with Estimated Annual Percentage Changes (EAPCs) recorded at 0.42 (0.41–0.43) for females and 0.11 (0.09–0.12) for males, respectively, and Average Annual Percentage Changes (AAPCs) of 0.44 (95% CI: 0.43–0.45) for females compared to 0.13 (95% CI: 0.12–0.14) for males. In 2021, the YLDs rate decreased as the Socio-Demographic Index (SDI) increased across 224 countries, indicating a concentration of the burden in countries with a medium SDI. Between 1990 and 2021, the incidence of ONIHL among females exhibited an upward trend in most countries, whereas among males, it predominantly reflected a downward trend. The decomposition analysis revealed that population growth was the primary factor contributing to the increase in YLDs. Projections indicate that by 2036, the YLDs rate for ONIHL will reach 103.45 per 100,000 in males and 74.19 per 100,000 in females.ConclusionThe global burden of ONIHL is rising at a concerning rate, particularly in countries with a medium SDI and among females. Therefore, it is imperative to implement targeted health education, regular screenings, and accessible hearing protection measures to mitigate the risks associated with ONIHL, specifically for females.